Addition of gemcitabine to paclitaxel, epirubicin, and cyclophosphamide adjuvant chemotherapy for women with early-stage breast cancer (tAnGo): final 10-year follow-up of an open-label, randomised, phase 3 trial. Issue 6 (June 2017) - Earl, Helena M; Hiller, Louise; Howard, Helen C; Dunn, Janet A; Young, Jennie; Bowden, Sarah J; McDermaid, Michelle; Waterhouse, Anna K; Wilson, Gregory; Agrawal, Rajiv; O'Reilly, Susan; Bowman, Angela; et al.
Summary: Background: The tAnGo trial was designed to investigate the potential role of gemcitabine when added to anthracycline and taxane-containing adjuvant chemotherapy for early breast cancer. When this study was developed, gemcitabine had shown significant activity in metastatic breast cancer, and there was evidence of a favourable interaction with paclitaxel. Methods: tAnGo was an international, open-label, randomised, phase 3 superiority trial that enrolled women aged 18 years or older with newly diagnosed, early-stage breast cancer who had a definite indication for chemotherapy, any nodal status, any hormone receptor status, Eastern Cooperative Oncology Group performance status of 0–1, and adequate bone marrow, hepatic, and renal function. Women were recruited from 127 clinical centres and hospitals in the UK and Ireland, and randomly assigned (1:1) to one of two treatment regimens: epirubicin, cyclophosphamide, and paclitaxel (four cycles of 90 mg/m 2 intravenously administered epirubicin and 600 mg/m 2 intravenously administered cyclophosphamide on day 1 every 3 weeks, followed by four cycles of 175 mg/m 2 paclitaxel as a 3 h infusion on day 1 every 3 weeks) or epirubicin, cyclophosphamide, and paclitaxel plus gemcitabine (the same chemotherapy regimen as the other group, with the addition of 1250 mg/m 2 gemcitabine to the paclitaxel cycles, administered intravenously as a 0·5 h infusion on days 1 and 8 every 3 weeks). Patients were randomly assigned by a central computerised deterministic minimisation procedure, with stratification by country, age, radiotherapy intent, nodal status, and oestrogen receptor and HER-2 status. The primary endpoint was disease-free survival and the trial aimed to detect 5% differences in 5-year disease-free survival between the treatment groups. Recruitment completed in 2004 and this is the final, intention-to-treat analysis. This trial is registered with EudraCT (2004-002927-41), ISRCTN (51146252), andClinicalTrials.gov (NCT00039546 ). Findings: Between Aug 22, 2001, and Nov 26, 2004, 3152 patients were enrolled and randomly assigned to epirubicin, cyclophosphamide, paclitaxel, and gemcitabine (gemcitabine group; n=1576) or to epirubicin, cyclophosphamide, and paclitaxel (control group; n=1576). 11 patients (six in the gemcitabine group and five in the control group) were ineligible because of pre-existing metastases and were therefore excluded from the analysis. At this protocol-specified final analysis (median follow-up 10 years [IQR 10–10]), 1087 disease-free survival events and 914 deaths had occurred. Disease-free survival did not differ significantly between the treatment groups at 10 years (65% [63–68] in the gemcitabine group vs 65% [62–67] in the control group), and median disease-free survival was not reached (adjusted hazard ratio 0·97 [95% CI 0·86–1·10], p=0·64). Toxicity, dose intensity, and a detailed safety substudy showed both regimens to be safe, deliverable, and tolerable. Grade 3 and 4 toxicities were reported at expected levels in both groups. The most common were neutropenia (527 [34%] of 1565 patients in the gemcitabine group vs 412 [26%] of 1567 in the control group), myalgia and arthralgia (207 [13%] vs 186 [12%]), fatigue (207 [13%] vs 152 [10%]), infection (202 [13%] vs 141 [9%]), vomiting (143 [9%] vs 108 [7%]), and nausea (132 [8%] vs 102 [7%]). Interpretation: The addition of gemcitabine to anthracycline and taxane-based adjuvant chemotherapy at this dose and schedule confers no therapeutic advantage in terms of disease-free survival in early breast cancer, although it can cause increased toxicity. Therefore, gemcitabine has not been added to standard adjuvant chemotherapy in breast cancer for any subgroup. Funding: Cancer Research UK core funding for Clinical Trials Unit at the University of Birmingham, Eli Lilly, Bristol-Myers Squibb, and Pfizer.